1977
DOI: 10.1126/science.841321
|View full text |Cite
|
Sign up to set email alerts
|

Species Identification in the North American Cowbird: Appropriate Responses to Abnormal Song

Abstract: Female cowbirds raised in auditory isolated from males responded to the songs of male cowbirds with copulatory postures. The songs of males reared in isolated were more effective in eliciting the posture than the songs of normally reared males. The females did not respond to the songs of other species. These results indicate one mechanism of species identification for this parasitic species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
106
0

Year Published

1982
1982
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 227 publications
(110 citation statements)
references
References 1 publication
4
106
0
Order By: Relevance
“…Many attempts have been made to uncover a recognition signal between young and adult cowbirds (Göth & Hauber, 2004;Hauber, Russo, & Sherman, 2001). This study thus joins with others in finding no privileged recognition mechanism (see King & West, 1977) and adds weight to Hauber, Sherman, and Parprika's (2000) account of cowbird recognition as being multifaceted.…”
Section: Reactions To Adultssupporting
confidence: 79%
“…Many attempts have been made to uncover a recognition signal between young and adult cowbirds (Göth & Hauber, 2004;Hauber, Russo, & Sherman, 2001). This study thus joins with others in finding no privileged recognition mechanism (see King & West, 1977) and adds weight to Hauber, Sherman, and Parprika's (2000) account of cowbird recognition as being multifaceted.…”
Section: Reactions To Adultssupporting
confidence: 79%
“…However, in an experiment with captive birds including four males and two females, I found a straight-line hierarchy (Darley 1978). Also King and West (1977) stated "Data from our laboratory indicated that cowbirds have highly structured dominance hierarchies and complex intraspecific behaviors that may also facilitate identification or maintain social integration among acquainted cowbirds." Some field data supported this view.…”
Section: Discussionmentioning
confidence: 99%
“…This display can be considered a combination of sexual proceptivity and receptivity. A solicitation display assay (SDA) is commonly used in passerine research to quantify the responsiveness of females to song (King and West, 1977;Brenowitz, 1991;Searcy, 1992). Given the potential for interactions of GnIH and the two avian GnRHs, we sought to determine what effects centrally administered GnIH might have on the known functional outputs of cGnRH-I (gonadotropin release) and cGnRH-II (copulation solicitation).…”
Section: Introductionmentioning
confidence: 99%